PERSPEKTIF VIKTIMOLOGIS BAGI PEKERJA RUMAH TANGGA DALAM HAL KELAYAKAN BEKERJA - Leni Widi Mulyani (JURNAL LITIGASI (e-Journal), 2018)
Domestic Workers (PRT) are very helpful figures in the household, a clean and healthy home will provide a comfortable atmosphere for the whole house. The duties of domestic workers are so important that the International Labor Organization (ILO) regulates their rights in ILO Convention No. 189 concerning Decent Work For Domestic Workers. However, on the other hand, the reality is actually far from what is stipulated in the convention. In Indonesia, there are still many violations of rights against them. This article seeks to discuss the legal position of domestic workers according to Law No. 13 of 2003 concerning Manpower and the position of domestic workers in the perspective of victimization and legal protection for domestic workers and the urgency of the Protection Act for Domestic Workers. The absence of national laws in terms of protection for domestic workers has made this group victims. Conditions of working hours and wages that have no clear rules have placed domestic workers as victims. Keywords: Domestic Workers, Eligibility to Work.